Building and validating attention deficit and hyperactivity disorder scale in the Saudi environment according to the diagnostic and statistical manual of mental disorders (5th edition) - Gaber, Sherif Adel (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to verify the psychometric properties of the attention deficit and hyperactivity disorder scale, among a sample of Saudi children. The researcher designed the instrument of study according to the Saudi environment. The sample consisted of (1120) boys and girls who are enrolled in a number of primary and middle schools in the governorates (Al- Ahsa, Riyadh, and Tabuk). The findings of the study revealed that the attention deficit and hyperactivity disorder scale has interceder reliability, face and factorial validity, and has high reliability by using Cronbach’s alpha, and method of split- half. The study recommended on one hand to use the attention deficit and hyperactivity disorder scale in the study community, and extract of local criteria on the other hand.